A new mouse anti-mouse complement receptor type 2 and 1 (CR2/CR1) monoclonal antibody as a tool to study receptor involvement in chronic models of immune responses and disease. Issue 2 (February 2015) - Kulik, Liudmila; Hewitt, Finnegan B.; Willis, Van C.; Rodriguez, Rosa; Tomlinson, Stephen; Michael Holers, V.
Highlights We generated a new monoclonal mouse anti-mouse complement receptor type 2/complement receptor type 1 (CR2/CR1) antibody, designated mAb 4B2. mAb 4B2 antibody blocks binding of the C3dg ligand to CR2. In vivo injected mAb 4B2 induces partial down regulation of CR1 and a more substantial elimination of CR2 from B cells without inducing B cell death or elimination. In vivo injection of mAb 4B2 antibody decreases humoral immune responses to T dependent antigens. mAb 4B2 can be used at various time points in murine chronic models of human autoimmune and inflammatory diseases to assess the role of receptor-ligand interactions in the further evolution of disease.